2020
DOI: 10.1111/ijn.12908
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in nurses working in China: A national questionnaire survey

Abstract: Aim This study aimed to assess the overall status of burnout in nurses in China on a national scale and investigate the demographic characteristics related to burnout and the relationships between demographics, job satisfaction and burnout. Methods This was a national cross‐sectional study conducted by the Chinese Nursing Association between July 2016 and July 2017. Data were collected using a structured, self‐administered questionnaire. Results A total of 51 406 registered nurses in 311 Chinese cities complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 31 publications
5
35
4
4
Order By: Relevance
“…Respondents with high levels of EE, DP and low PA were 423 (40.1%), 384(36.4%) and 594 (56.3%), respectively. Our results were consistent with the previous studies for Chinese doctors and nurses [8,9]. For the burnout definitions and criteria are diverse [4], it is difficult to compare burnout rates directly between studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Respondents with high levels of EE, DP and low PA were 423 (40.1%), 384(36.4%) and 594 (56.3%), respectively. Our results were consistent with the previous studies for Chinese doctors and nurses [8,9]. For the burnout definitions and criteria are diverse [4], it is difficult to compare burnout rates directly between studies.…”
Section: Discussionsupporting
confidence: 91%
“…For the burnout definitions and criteria are diverse [4], it is difficult to compare burnout rates directly between studies. But it is clear that Chinese medical staff suffered with the high prevalence of burnout [9,[39][40][41]. Compared with a previous burnout study in Liaoning province in 2013 [15], our result of high burnout was much higher (20.5% verse 12.1%).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…This can be explained as RACFs offering higher salaries for a greater likelihood of better financial resources and higher employee retention. Furthermore, it is well documented that nurses with relatively low incomes are more likely to report higher job burnout, 72 lower prestige, less professional autonomy, 73 and lower work creativity, which may lead to less empathic care delivery, and missing or rushed care. A national survey of 239,312 employees in China RACF settings also revealed that the labor (taking care of six to seven disabled or semi-disabled older adults on average every day) and payment (<3000 RMB) for nursing staff were significantly unbalanced, which leads to a continual decline in their efforts and attitudes toward nursing development and career retention.…”
Section: Discussionmentioning
confidence: 99%